Effect of bentonite application on the morphological, physiological, and biochemical behaviour of Triticum durum Desf and Triticum aestivum L. cultivated in saline soils - Mohammed El Amine Bachir Bouiadjra; Malika Ghellai; Ahmed Megharbi; Seher Bahar Aciksoz; Abdesselem Si Mohammed; José Galian (Universitas Sebelas Maret, 2025)
Soil salinity represents a major constraint to agricultural productivity in arid and semi-arid regions, severely affecting cereal growth and yield. This study evaluated the effect of mineral soil amendments using two types of bentonite, sodium bentonite from Mostaganem (B-Na) and calcium bentonite from Maghnia (B-Ca), on the morphological, physiological, and biochemical responses of durum wheat Triticum durum Desf. And bread wheat Triticum aestivum L. cultivated in saline soil 19 dS.m⁻¹ from the Relizane region (western Algeria). Greenhouse experiments were conducted using bentonite doses of 5% and 10% (w/w) to assess plant growth parameters, relative water content (RWC), chlorophyll pigments, and soluble sugar levels. Both bentonites enhanced wheat performance under saline conditions, with the 5% dose producing the most favourable effects. Notably, 5% B-Na significantly increased RWC, chlorophyll concentration, and soluble sugar content in T. aestivum compared with the saline control. Excessive amendment (10%) did not yield further benefits. These findings suggest that moderate application of bentonite can effectively alleviate salinity stress and improve physiological performance in wheat. The study emphasizes the importance of optimizing bentonite type and dose based on soil characteristics and crop sensitivity to salinity.